Justification of the integrated approach to management of HIV-infected patients with comorbid pathology of the digestive system - Holubovska, Olga; Vysotskyi, Volodymyr (Psychosomatic Medicine and General Practice, 2020)
Introduction. Among the main strategic and operational goals of the State Strategy for Combating HIV / AIDS, Tuberculosis and Viral Hepatitis by 2030 in Ukraine is to ensure comprehensive access to HIV treatment, increase the effectiveness of monitoring and support of treatment of both opportunistic infections and other somatic conditions in HIV-infected patients. The key role of family physicians in the detection and treatment of many chronic gastrointestinal complications in HIV-infected patients is recognized. Purpose of the study. To increase the efficiency of early diagnosis and tactics of integrated management of HIV-infected patients of family physicians (FP) by clarifying the peculiarities of HIV infection in the presence of comorbid pathology of the digestive system (DS) and creating an algorithm for providing medical care to these patients. Material and methods. The research was conducted on the basis of five regional HIV / AIDS centers of Ukraine during 2017-2019. Randomly selected 342 adult HIV-infected patients were divided into two groups - with concomitant lesions and without concomitant gastrointestinal lesions. The following research methods were used: general clinical and laboratory biochemical, molecular genetic, immunological, enzyme-linked immunosorbent, instrumental (FGDS, chest radiography, abdominal ultrasound, computed tomography of the chest and / or abdominal cavity), analysis of primary medical records, consultations related specialists according to the indications, questionnaires, statistical methods. Results and discussion. It was found that the incidence of gastrointestinal pathology in patients with II, III and IV clinical stages of HIV infection was significantly higher than in patients with stage I, significantly more often associated with tuberculosis, candidiasis, kidney disease and HIV encephalopathy and was combined. Manifestations of asthenovegetative and dyspeptic syndromes, weight loss, anemia and leukopenia, increased activity of liver enzymes, low levels of CD4 + lymphocytes and preservation of viral load on antiretroviral therapy were significantly more common in HIV-infected patients with gastrointestinal pathology. In the presence of pathology of the digestive system, replacements, breaks and side effects of antiretroviral therapy were significantly more frequent. The results of physicians survey analysis showed the role of family physicians in the current examination and management of HIV-infected people with comorbid pathology of the digestive system. Conclusions. To detect diseases of the organs of the DS in HIV-infected people, it is necessary to conduct a comprehensive laboratory and instrumental examination, taking into account the possibility of combined pathology. The proposed algorithm of integrated management of HIV-infected patients with comorbid pathology of DS by FPs, taking into account the most informative clinical and laboratory criteria, allows to increase the effectiveness of early diagnosis and tactics of integrated management of HIV-infected by FPs.